Design and synthesis of novel 1, 2-dithiolan-4-yl benzoate derivatives as PTP1B inhibitors. Issue 10 (15th May 2015) - Chen, Jing; Gao, Li-Xin; Gong, Jing-Xu; Jiang, Cheng-Shi; Yao, Li-Gong; Li, Jing-Ya; Li, Jia; Xiao, Wei; Guo, Yue-Wei
Graphical abstract